The determinants of luxury brand stories on online repurchase intentions among gen Z in China - Zhang, Tianyang; Lee, Khai Loon; Puteri Fadzline, Muhamad Tamyez (Global Academic Excellence (M) Sdn. Bhd., 2025)
The rise of Gen Z as a dominant consumer segment and the rapid expansion of e-commerce have prompted luxury brands to adopt innovative storytelling strategies to engage and retain this digitally savvy audience. This study explores the impact of luxury brand stories on online repurchase intentions among Gen Z consumers in China, emphasizing the role of narratives in shaping emotional connections, trust, and loyalty. Using a qualitative research approach, this study conducted in-depth interviews with Gen Z consumers who have previously purchased luxury brands online. The findings reveal that authentic and emotionally engaging brand stories significantly influence repurchase intentions by fostering a sense of trust and alignment with personal values. Narratives that highlight sustainability, inclusivity, and cultural relevance were found to resonate strongly with Chinese Gen Z consumers, who prioritize both ethical considerations and social identity in their purchasing decisions. This research contributes to the literature by offering nuanced insights into how luxury brand storytelling drives consumer loyalty in the digital age, particularly within the unique socio-cultural context of China. The study provides practical recommendations for luxury brands seeking to refine their storytelling strategies to cultivate lasting relationships with Gen Z consumers and enhance their competitive positioning in the online market.